Impact of donor–recipient sex match on long‐term survival after heart transplantation in children: An analysis of 5797 pediatric heart transplants. (22nd December 2015) - Kemna, Mariska; Albers, Erin; Bradford, Miranda C.; Law, Sabrina; Permut, Lester; McMullan, D. Mike; Law, Yuk
Abstract: The effect of donor–recipient sex matching on long‐term survival in pediatric heart transplantation is not well known. Adult data have shown worse survival when male recipients receive a sex‐mismatched heart, with conflicting results in female recipients. We analyzed 5795 heart transplant recipients ≤18 yr in the Scientific Registry of Transplant Recipients (1990–2012). Recipients were stratified based on donor and recipient sex, creating four groups: MM (N = 1888), FM (N = 1384), FF (N = 1082), and MF (N = 1441). Males receiving sex‐matched donor hearts had increased unadjusted allograft survival at five yr (73.2 vs. 71%, p = 0.01). However, this survival advantage disappeared with longer follow‐up and when adjusted for additional risk factors by multivariable Cox regression analysis. In contrast, for females, receiving a sex‐mismatched heart was associated with an 18% higher risk of allograft loss over time compared to receiving a sex‐matched heart (HR 1.18, 95% CI: 1.00–1.38) and a 26% higher risk compared to sex‐matched male recipients (HR 1.26, 95% CI: 1.10–1.45). Females who receive a heart from a male donor appear to have a distinct long‐term survival disadvantage compared to all other groups.